THE ROLE OF NURSING SUPERVISION ON CLINICAL NURSES' JOB SATISFACTION: SYSTEMATIC REVIEW - Nurma Lindawati; Nuzul Qur'aniati; Ilya Krisnana (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Clinical supervision is widely implemented to support learning, professional development, and performance evaluation among nurses. Although evidence suggests that clinical supervision improves nurses’ job satisfaction, the lack of standardized policies and guidelines limits its optimal implementation. Variations in supervision models, frequency, and duration highlight the need for a synthesized evidence base. Objective: This systematic review aimed to gather and examine studies investigating how supervision affects nurses' job satisfaction in clinical settings. Design: This is a systematic review. Data Sources: Electronic searches were conducted across four databases: Scopus, EBSCO, CINAHL, and PubMed. The search covered articles published between 2019 and 2024. Review Methods: The review followed PRISMA guidelines. A total of 380 articles were identified; duplicates were removed, and titles and abstracts were screened according to predefined criteria. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool, resulting in 15 eligible studies. Results: The findings indicate that clinical supervision significantly improves nurses’ job satisfaction, particularly when conducted regularly and in a structured manner. Scheduled supervision supports knowledge development, reduces work-related stress, and enhances skill acquisition, with positive effects lasting up to 3–6 months. Supervision provided by experienced peers was generally more effective than supervision by direct supervisors. However, substantial variation was observed in supervision models, frequency, and duration. Supervisor competence, organizational support, and a supportive supervision environment promoting teamwork, communication, and psychological safety were key factors influencing effectiveness. Conclusion: Clinical supervision positively influences nurses’ job satisfaction and contributes to improved quality of care. Nonetheless, variability in supervision practices highlights the need for further research to develop evidence-based and standardized clinical supervision guidelines that consider organizational and workplace contexts.